Exploration of the Use of Web-based Interactive Learning Media in the Merdeka Curriculum for Science and Social Studies (IPAS) Learning in Third-Grade Elementary School - Nanda, Dodi Widia; Hasibuan, Rusdi Indra; Sakinah, Sakinah (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
The exploration of technological advancements in the field of education has introduced innovative digital-based learning media, one of which is the Game Educaplay. This media is considered to enhance student engagement interactively, particularly in the context of the Merdeka Curriculum, which emphasizes active, enjoyable, and student-centered learning. In the context of Science and Social Studies (IPAS) learning for third-grade elementary school students, this media has the potential to facilitate understanding of the material and create a more engaging and effective learning environment. This study aims to explore the use of interactive web-based learning media using Game Educaplay in IPAS learning for third-grade students under the Merdeka Curriculum and to understand the perceptions of teachers and students regarding this media. This research employs a qualitative approach with a case study method. Data collection techniques include interviews, observations, and documentation at SD Negeri 15 Koto Baru, with subjects including the class teacher and third-grade students. The results of the study indicate that the use of Game Educaplay can make learning more effective, assist group work, increase student enthusiasm and motivation, facilitate the evaluation process, and reinforce understanding of the material. Both teachers and students gave positive responses to this media, making it an innovative alternative that supports IPAS learning in the implementation of the Merdeka Curriculum.